A Rare Case of Perforated Meckel’s Diverticulum - Vijay P Agrawal; Yunus Shah (Journal of Clinical and Biomedical Sciences)
We present a rare case of perforated Meckel’s diverticulum which presented initially with subcutaneous abscess. The abscess ruptured spontaneously and formed an enterocutaneous fistula and later presented as perforation peritonitis. Keywords: Meckel’s diverticulum, enterocutaneous fistula, perforation peritonitis